Ethnomedicinal survey of medicinal plants used in the management of diabetes in Ibadan north east and south east, Oyo state, Nigeria (2022)
Diabetes mellitus, a lifestyle disease, affects 8.3% of the world’s adult population. It is one of the most frequent non-communicable diseases in the modern period with enormous burden due to changes in lifestyle, eating habits, the aging population, and urbanization. This work aimed to document the ethnomedicinal plants used in the management of diabetes among Traditional Medical Practitioners (TMPs), herb dealers, and persons with claims of medicinal plant knowledge in two regions of Ibadan. Data was collected from 100 respondents using a semi-structured questionnaire. Data was examined using descriptive statistics and quantitative ethnobotanical indices. Majority of responders (94%) were females with little or no formal schooling (60%). Sixty plant species belonging to 35 families, and 57 genera were found to be used as antidiabetics in the study areas. The most prominent, being Hunteria umbellata, with the highest Use of Mention Index (UMI-0.56). Plants from the Fabaceae family were most mentioned (23%). The most regularly used plant part is the leaves (25%). Oral route was the main means of administration, with decoction being the most preferred method of preparation. The southwestern Nigeria is rich in unknown plants effective in diabetes control, however, more research is needed to extract, chemically clarify, and describe bioactive components that could be used as lead for the development of new antidiabetic medicines with favorable efficacy and safety profiles.